2023
DOI: 10.1111/mec.16870
|View full text |Cite
|
Sign up to set email alerts
|

Telomerase as a possible key to bypass reproductive cost

Abstract: Three widely accepted assumptions are based on telomere research in human cells:(i) telomere length is a determinant of replicative ageing; (ii) telomerase activity in somatic cells supports the proliferative capacity of the cells and thus contributes to their regenerative potential and is a determinant of organismal lifespan; and (iii) the lack of telomerase activity acts as a tumour suppression mechanism. However, from a broader view, the link between telomere biology and cellular and organismal ageing, as w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 154 publications
0
4
0
Order By: Relevance
“…Given the generally high levels of TA at most sampling points however, it is possible that telomerase has other non-canonical functions in this species (Arndt and MacKenzie, 2016). It has been suggested previously that telomerase may be involved in processes as diverse as mitochondrial function (Ahmed et al, 2008;Haendeler et al, 2009;Moslehi et al, 2012), reproduction (Hapangama et al, 2008;Tan et al, 2012;Čapková Frydrychová, 2023), and immunity (Allsopp et al, 2002;Blasco, 2002). Garden dormice may be a good model for investigating such non-canonical functions given the high activity we have detected in this study and their life history which is strongly linked to seasonal fluctuations in energy availability, temperature, and predator avoidance.…”
Section: Discussionmentioning
confidence: 92%
“…Given the generally high levels of TA at most sampling points however, it is possible that telomerase has other non-canonical functions in this species (Arndt and MacKenzie, 2016). It has been suggested previously that telomerase may be involved in processes as diverse as mitochondrial function (Ahmed et al, 2008;Haendeler et al, 2009;Moslehi et al, 2012), reproduction (Hapangama et al, 2008;Tan et al, 2012;Čapková Frydrychová, 2023), and immunity (Allsopp et al, 2002;Blasco, 2002). Garden dormice may be a good model for investigating such non-canonical functions given the high activity we have detected in this study and their life history which is strongly linked to seasonal fluctuations in energy availability, temperature, and predator avoidance.…”
Section: Discussionmentioning
confidence: 92%
“…However, the growing list of alternative nuclear and extranuclear functions attributed to telomerase/TERT calls for new perspectives on this pleiotropic enzyme. Recent research in honeybees and termites suggests that telomerase may also play non-canonical roles in these eusocial insects, which appears to be related to the exceptional longevity of kings and queens (Korandová & Čapková Frydrychová, 2016; Koubová et al ., 2021), reviewed in (Čapková Frydrychová, 2023). Our previous research in several termite species has shown that their long-lived reproductive castes have high enzymatic activities of telomerase and TERT abundance in their somatic tissues, including post-mitotic organs.…”
Section: Discussionmentioning
confidence: 99%
“…Telomere-telomerase system has received great attention as a potentially universal lifespan regulator at cell and ultimately organismal level, with multiple evidence in humans, some other mammals and birds (Sahin & DePinho, 2010; Jaskelioff et al ., 2011; Heidinger et al ., 2012). Yet, research conducted across the phylogenetic diversity of animals has shown that the importance of telomere shortening and telomerase for lifespan control differ among animal lineages depending on various life history traits, such as type of postembryonic development (determinate vs. indeterminate growth), body size, general lifespan, and others (reviewed, e.g., in Smith et al ., 2022; Čapková Frydrychová, 2023). Telomere lengths and telomerase activities may thus be efficient predictors of life expectancies in some taxa and poor in others.…”
Section: Introductionmentioning
confidence: 99%
“…They make the case that analyses of the sugars, or glycans, that coat host cell surface macromolecules will be critical for increasing the accuracy of risk assessment. In another broadly important Opinion paper, Čapková Frydrychová (2023) argues that key assumptions about telomere biology and aging do not hold up when considered across a wide range of taxa, but suggests that discrepancies can be resolved when considered in the context of organismal reproductive strategies.…”
Section: Highlights Of 2023mentioning
confidence: 99%